Odpowiedzi

Najlepsza Odpowiedź!
2010-01-10T18:33:31+01:00
(b) 3-3x/2=5/8-4x-3/6 odejmuje 3
-3x/2 = 5/8 - 4x-3/6 - 3 mnoże przez 2
-3x = 10/8 - 4x-3/3 - 6
-3x + 4x-3/3 = 10/8 - 6
-3x + 4/3 x - 1 = 10/8 - 6
-5/3 x = 10/8 - 6 +1
- 5/3 x = -3,75
x = 2,25

licze na naj (;
2010-01-10T18:39:42+01:00
3-3x/2=5/8 - (4x-3)/6 |*6
18-9x=15/4 - (4x - 3)
18-9x=15/4-4x+3 |+9x
18=27/4+5x |-(27/4)
5x=18-6 3/4
5x=11 1/4 |:5
x=(45/4):5
x=(45/4)*(1/5)
x=9/4
x=2 1/4
2010-01-10T18:42:16+01:00
3-(3x:2)=(5:8) - (4x-3) :6
3-1,5X= 5/8 - 2/3X + 1/2
-1,875= 1,5X -2/3X
-1,875=0,8(3)X
X=2,25